Կորուսյա՞ լ, թե՞ ուսյալ սերունդ․ Երիտասարդները հետպատերազմյան իրականությունում - Գալստյան, Մարինա
Հոդվածը անդրադառնում է հետպատերազմյան հասարակությունների վերաբերյալ սոցիոլոգիական մտքի զարգացմանը՝ վերլուծելով կոնֆլիկտի տեսական մոտեցումների, ռազմական սոցիոլոգիայի առանձնահատկությունները։ Հոդվածը ներկայացնում է հետպատերազմյան հասարակությունների վերաբերյալ սոցիոլոգիական ուղենիշային աշխատությունները՝ ընդգծելով հետպատերազմյան իրականությունում երիտասարդների խնդիրների ուսումնասիրման փորձերը։ Բոսնիա-Հերցեգովինայի, բրիտանական, խորհրդային, հայկական հետպատերազմյան հասարակությունների փորձի վերլուծության միջոցով հոդվածն առանձնացնում է հետպատերազմյան հասարակություններին բնութագրող կողմերը, որոնք են՝ նախկին արժեքների վերանայումը, ազատության, անձնական պատասխանատվության զգացման մեծացումը սեփական անձի և փոքր խմբի նկատմամբ, քննադատական մտածողության մակարդակի բարձրացումը, սոցիալական տարբեր շերտերի միջև հաղորդակցության հնարավորությունների և փորձառության մեծացումը, սոցիալ-տնտեսական խնդիրների սրումը՝ ժողովրդագրական խնդիրներ, պատերազմի մասնակիցների խնդիրներ՝ բնակարանային պայմաններ, գործազրկություն, առողջական խնդիրներ, երիտասարդների՝ «լռելու», «պատերազմող մեծահասակներից» տարանջատվելու միտումը և պրակտիկան։ В статье рассматриваются развитие социологической подходы о послевоенных обществах, анализируются особенности теоретических подходов к конфликтологии и военной социологии. В статье представлены знаковые социологические работы о послевоенных обществах, сделан акцент на попытках изучения проблем молодежи в послевоенной действительности. Анализируя опыт послевоенных обществ Боснии и Герцеговины, Великобритании, Советского Союза и Армении, в статье выделяются аспекты, характеризующие послевоенные общества, а именно: пересмотр прежних ценностей, усиление чувства свободы, личная ответственность перед собственной личностью в малых группах, повышение уровня критического мышления, обострение демографических проблем, жилищных условий, безработицы, проблем со здоровьем, склонность и практика молодежи «молчать», отделяться от «воюющих взрослых». The article discusses the development of sociological thought about post-war societies, analyzing the features of theoretical approaches to conflict and military sociology. The article presents the landmark sociological works on post-war societies emphasizing the attempts to study the problems of young people in the post-war reality. By analyzing the experience of Bosnia Herzegovina, British, Soviet, and Armenian post-war societies, the article highlights the aspects that characterize post-war societies, which are: revision of previous values, increasing sense of freedom, personal responsibility towards a small group, increasing the level of critical thinking, demographic problems, housing conditions, unemployment, health problems, the tendency and practice of young people to "keep silent", to separate themselves from "adults". After the 2020 Artsakh war, the impact of the war's consequences on young people has not yet been fully and deeply studied. The article also provides empirical insights from nationwide survey among Armenian youth. The survey results showed that the goals of young people in particular have changed, the vast majority of young people who participated in the survey, stated that their aspirations and goals changed significantly after the war. Moreover, after the war, the majority of young people had to reduce their aspirations and goals and adapt to the post-war situation. It is also interesting that Armenian young people stated that in crisis and difficult situations they try to find new and interesting solutions to face problems. So in the post-war reality, we can define Armenian youth not as a "lost" but as a "found" generation.
Keywords: Սոցիոլոգիա